Comparison of implant quality between intraoperatively built custom-linked seeds and loose seeds in permanent prostate brachytherapy using sector analysis - Katayama, Norihisa (J Radiat Res, 2016)
We compared the implant quality of intraoperatively built custom-linked (IBCL) seeds with loose seeds in permanent prostate brachytherapy. Between June 2012 and January 2015, 64 consecutive prostate cancer patients underwent brachytherapy with IBCL seeds (n = 32) or loose seeds (n = 32). All the patients were treated with 144 Gy of brachytherapy alone. Brachytherapy was performed using a dynamic dose calculation technique. Computed tomography/magnetic resonance imaging fusion-based dosimetry was performed 1 month after brachytherapy. Post-implant dose–volume histogram (DVH) parameters, prostate sector dosimetry, operation time, seed migration, and toxicities were compared between the IBCL seed group and the loose seed group. A sector analysis tool was used to divide the prostate into six sectors (anterior and posterior sectors at the base, mid-gland, and apex). V100 (95.3% vs 89.7%; P = 0.014) and D90 (169.7 Gy vs 152.6 Gy; P = 0.013) in the anterior base sector were significantly higher in the IBCL seed group than in the loose seed group. The seed migration rate was significantly lower in the IBCL seed group than in the loose seed group (6% vs 66%; P < 0.001). Operation time per seed was significantly longer in the IBCL seed group than in the loose seed group (1.31 min vs 1.13 min; P = 0.003). Other post-implant DVH parameters and toxicities did not differ significantly between the two groups. Our study showed more dose coverage post-operatively in the anterior base prostate sector and less seed migration in IBCL seed implantation compared with loose seed implantation.